VALUE ENGINEERING DAN STRATEGI BISNIS PADA PT ANGKASA PURA II - Slamet Priyanto; Hadi Suharno; Haryono Haryono (Institut Transportasi dan Logistik Trisakti, 2016)
This research aims to determine the business model that is currently running, knowing Maps Strategy and Operation Process Map companies towards World Class Airport Company, then analyzing step Value Engineering up to level 1 (one) that needs to be done to improve the strength of the company. The method used is descriptive qualitative and quantitative methods are combined with observations and structured interviews so as to portray phenomena that there is both natural and human engineering. The implementation strategy of Value Engineering on this research, expected changes in the strength of the company to be much better in the period 2015-2016 exceeded even the expectations that have been established in 2012-2016 RJPP PT Angkasa Pura II (Persero).